The Perception of Audit Quality Among Financial Statements Users, Preparers and Auditors, In Tunisia - Mouna Hamza; Damak-Ayadi (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Question- The principal purpose of this research is to determine the audit quality attributes as perceived by the different stakeholders: financial statements users, preparers and auditors in Tunisia. Motivation- Audit markets have been weakened by recent financial scandals. This led to debates about the concept of audit quality and its evaluation. As the evaluation of audit quality through auditor quality is today unable to allow a real evaluation of the adequacy of the realized audit tasks, we believe that the evaluation of audit quality must henceforth include new components such as characteristics related to audit firms, external factors and legislation. Data- We used a 5-point Likert scale questionnaire; a measurement scale of the audit quality attributes. Our sample contained the three groups of stakeholders in order to compare their perceptions of audit quality. We distributed 380 questionnaires. Our return rate was 38%. Each questionnaire contained 40 attributes organized in five factors (characteristics related to auditor, characteristics related to audit firm, control of the profession, legislation, external factors). Tools- Factor Analysis method was used to reduce the number of items to a smaller set of factors and to summarize information Findings- This study shows that characteristics related to auditor and characteristics related to audit firm were generally perceived to be the most important. Moreover, this study underlines the importance of the control of the profession. The legislation factor is only significant for the users of the financial statements and the preparers. Contribution- While numerous studies have examined audit quality, many have focused on eliciting the attributes of audit quality from auditors. However, as the competitive environment increases, understanding the perceptions of financial statements users, preparers, and auditors regarding audit quality becomes increasingly important. Differences in perceptions may provide insight for audit firms to enhance satisfaction for both groups and improve overall audit quality. Our study is a comprehensive attempt to compare the perceptions of different stakeholder with regard to audit quality.
Keywords: M42; 650; audit quality; stakeholder theory; agency theory; signal theory; Factors Analysis; Tunisian context